1964
DOI: 10.1139/f64-097
|View full text |Cite
|
Sign up to set email alerts
|

Some Characteristics of Nitinat Lake, An Inlet on Vancouver Island, British Columbia

Abstract: Tests for migratory hstory of the New Zealand common smelt (Retropinna retropinna (Richardson)) using otolith is0 topic composition Northcote TG, Hendy CH, Nelson CS, Boubee JAT. Tests for migratory history of the New Zealand common smelt (Retropinna retropinna (Richardson)) using otolith isotopic composition.Ecology of Freshwater Fish 1992: 1: 61-72. 0 1992 Munksgaard Abstract -Stable oxygen and carbon isotopic analyses were made for water at 24 sites, mainly from the Waikato watershed (North Island, New Zeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1967
1967
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The physical and chemical features of Lake Nitinat have been described by NORTHCOTE, WILSON and HURN (1964) and by RICHARDS, CLINE, BROENKOW and ATKINSON (1965). The restricted entrance and freshwater influx result in a strong halocline that restricts vertical circulation so that anoxic conditions develop below about 30 m. Hydrogen sulfide concentrations increase with depth, reaching more than 300 ~g-atom S 2--S/1.…”
Section: Environments Where Methane Has Been Observedmentioning
confidence: 99%
“…The physical and chemical features of Lake Nitinat have been described by NORTHCOTE, WILSON and HURN (1964) and by RICHARDS, CLINE, BROENKOW and ATKINSON (1965). The restricted entrance and freshwater influx result in a strong halocline that restricts vertical circulation so that anoxic conditions develop below about 30 m. Hydrogen sulfide concentrations increase with depth, reaching more than 300 ~g-atom S 2--S/1.…”
Section: Environments Where Methane Has Been Observedmentioning
confidence: 99%
“…They showed that Nitinat Lake was a rather extreme example of the local fjords, the bottom waters of which are sometimes not renewed for a number of years, so that temporary anoxia may occur. Northcote et al (1964) found that a sharp pycnocline existed in the upper 10 m of Nitinat Lake and that the water below about 20-50 m was anoxic. It was not clear at the time of this study whether the anoxia was temporary or permanent; subsequent researchers suggested the latter.…”
mentioning
confidence: 98%
“…Average fjord depth (volume/surface area) is about 100 m (Northcote et al 1964). Nitinat Lake is separated from the ocean by the Narrows, a shallow channel (depths 2-5 m at low tide) some 3 km in length that measures as few as 60 m wide at the ocean entrance.…”
mentioning
confidence: 99%
“…As an example, consider the unusual return of chum salmon Oncorhynchus keta to Nitinat Lake on the west coast of Vancouver Island in 1972. Nitinat Lake is really a saline fjord with a very shallow sill at its mouth; its surface waters are made brackish and sometimes quite fresh by the inflow of the Nitinat River (Northcote et al 1964). Ordinarily, the return of chum salmon to the lake is too small to support a commercial fishery.…”
Section: Anomaliesmentioning
confidence: 99%